A nociceptor-specific RNAi screen in Drosophila larvae identifies RNA-binding proteins that regulate thermal nociception - Amber Dyson; Gita Gajjar; Katherine C. Hoffman; Dakota Lewis; Sara Palega; Erik Rangel Silva; James Auwn; Andrew Bellemer (PeerJ)
Nociception is the process by which sensory neurons detect and encode potentially harmful environmental stimuli to generate behavioral responses. Nociceptor neurons exhibit plasticity in which their sensitivity to noxious stimuli and subsequent ability to drive behavior may be altered by environmental conditions, injury, infection, and inflammation. In some cases, nociceptor sensitization requires regulated changes in gene expression, and recent studies have indicated roles for post-transcriptional mechanisms in regulating these changes as an aspect of nociceptor plasticity. The larvae of Drosophila melanogaster have been developed as a powerful model for studying mechanisms of nociception, nociceptor plasticity, and nociceptor development. Diverse RNA-binding proteins regulate the development and morphology of larval nociceptors, implying important roles for post-transcriptional regulation of gene expression in these neurons, but the importance of these mechanisms for nociceptive behavior has not been investigated systematically. In this study, we conducted a nociceptor-specific RNAi screen of 112 candidate RNA-binding protein genes to identify those that are required for normal sensitivity to noxious thermal stimuli. The screen and subsequent validation experiments identified nine candidate genes (eIF2α, eIF4A, eIF4AIII, eIF4G2, mbl, SC35, snf, Larp4B and CG10445) that produce defects in nociceptive response latency when knocked down in larval nociceptors. Some of the genes identified have well-understood roles in the regulation of translation initiation and regulation of nociceptor sensitization in vertebrate and invertebrate animal models, suggesting an evolutionarily conserved role for these mechanisms in regulating nociceptor sensitivity. Other screen isolates have previously described roles in regulating nociceptor morphology and mRNA processing, but less clear roles in regulating nociceptor function. Further studies will be necessary to identify the mechanisms by which the identified RNA-binding proteins regulate sensory neuron function and the identities of the mRNAs that they target.